HUBUNGAN STRATEGI PEMBELAJARAN, MOTIVASI DAN GAYA KOGNITIF DALAM KALANGAN SISWA GURU DI IPGKTHO - Mohd. Sopah, Faridah; Kayar, Rosly (Journal of Techno-Social, 2018)
The implementation of teaching and learning activities in Malaysia has a way of learning that is not comprehensive and often focuses on certain intelligence. Outwardly each individual has different features and not everyone has the same in terms of creative cognitive style and learning style strategy. Therefore, in this study, the researcher looks at the types of creative cognitive styles and the Self Regulated Learning used by students studying at the Teachers Institute. The instrument used is the Creative Cognitive Style questionnaire and the Self Regulated Learning Questionnaire is divided into two, namely the learning style and Motivation. The results of the study showed that most of the teacher’s students had the type of cognitive styles of adapters (98%) and only 2 (2%) who had low-level cognitive styles of innovators. The result of the correlation analysis showed that there was a very strong positive relationship between the Creative Cognitive Style and the Self Regulated Learning (r = 0.69). Therefore, this study finds that the Creative Cognitive Style is an element which indirectly influences the learning strategies among the students as long as they study at IPGKTHO Â Keywords: Creative Cognitive Style, Self Regulated Learning and Motivation